Complementarity of the 16S rRNA penultimate stem with sequences downstream of the AUG destabilizes the plastid mRNAs - Kuroda, Hiroshi (Oxford University Press, 2001)
Escherichia coli mRNA translation is facilitated by sequences upstream and downstream of the initiation codon, called Shine–Dalgarno (SD) and downstream box (DB) sequences, respectively. In E.coli enhancing the complementarity between the DB sequences and the 16S rRNA penultimate stem resulted in increased protein accumulation without a significant affect on mRNA stability. The objective of this study was to test whether enhancing the complementarity of plastid mRNAs downstream of the AUG (downstream sequence or DS) with the 16S rRNA penultimate stem (anti-DS or ADS region) enhances protein accumulation. The test system was the tobacco plastid rRNA operon promoter fused with the E.coli phage T7 gene 10 (T7g10) 5′-untranslated region (5′-UTR) and DB region. Translation efficiency was tested by measuring neomycin phosphotransferase (NPTII) accumulation in tobacco chloroplasts. We report here that the phage T7g10 5′-UTR and DB region promotes accumulation of NPTII up to ∼16% of total soluble leaf protein (TSP). Enhanced mRNA stability and an improved NPTII yield (∼23% of TSP) was obtained from a construct in which the T7g10 5′-UTR was linked with the NPTII coding region via a NheI site. However, replacing the T7g10 DB region with the plastid DS sequence reduced NPTII and mRNA levels to 0.16 and 28%, respectively. Reduced NPTII accumulation is in part due to accelerated mRNA turnover.